Responding to the grand challenges in healthcare via organizational innovation : needed advances in management research - Shortell, Stephen M. 1944-; Burns, Lawton R.; Hefner, Jennifer L. (Advances in health care management ;, 2022)
This book contains two Open Access chapters. The 21st volume of Advances in Health Care Management presents informed commentaries solicited from leaders across the field of health care management. Each chapter tackles a specific health care challenge, describing the state of the research on the challenge, identifying appropriate organizational innovations to respond to the challenge, and setting out a future research agenda. Expert authors consider what is known, what is not known, and what is needed to fill the gaps and advance knowledge. Responding to The Grand Challenges in Healthcare Via Organizational Innovation explores in detail varied scenarios and suggestions for dealing with unexpected crises, improving diversity, equity and inclusion in health care, building strategic alliances for inter-sector collaboration, as well as analyzing organizational governance and physician financial risk models.